Proposal for determing the scale of renovation needs of residential buildings = Propozycja określania skali potrzeb renowacji budynków mieszkalnych - Nowogońska, Beata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The scope of renovation works depends, above all, on the state in which a historical site has been preserved. All actions ought to be preceded by an assessment of the technical condition of the buildings. The article presents a method for determining the scale of needs for renovating existing buildings constructed in traditional technology.
Keywords: renowacja budynków; stan techniczny; stopień zużycia; potrzeby remontowe; renovation of buildings; technical condition; degree of wear; renovation needs